2010
DOI: 10.1155/2010/736907
|View full text |Cite
|
Sign up to set email alerts
|

Significant Growth Inhibition of Canine Mammary Carcinoma Xenografts following Treatment with Oncolytic Vaccinia Virus GLV-1h68

Abstract: Canine mammary carcinoma is a highly metastatic tumor that is poorly responsive to available treatment. Therefore, there is an urgent need to identify novel agents for therapy of this disease. Recently, we reported that the oncolytic vaccinia virus GLV-1h68 could be a useful tool for therapy of canine mammary adenoma in vivo. In this study we analyzed the therapeutic effect of GLV-1h68 against canine mammary carcinoma. Cell culture data demonstrated that GLV-1h68 efficiently infected and destroyed cells of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 18 publications
2
45
0
Order By: Relevance
“…Furthermore, a clinical trial with canine cancer patients has already been started. [3][4][5] canine distemper virus 6 and vaccinia virus strains, namely GLV-1h68, LIVP1.1.1 [7][8][9] and GLV-1h109 10 have been successfully tested for canine cancer therapy in preclinical settings (for review, see refs. 11 and 12).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a clinical trial with canine cancer patients has already been started. [3][4][5] canine distemper virus 6 and vaccinia virus strains, namely GLV-1h68, LIVP1.1.1 [7][8][9] and GLV-1h109 10 have been successfully tested for canine cancer therapy in preclinical settings (for review, see refs. 11 and 12).…”
Section: Introductionmentioning
confidence: 99%
“…All strains were derived from the GLV-1h68 oncolytic vaccinia virus strain (13). This strain was shown to be highly effective in numerous tumor models (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and is currently being tested for safety and efficacy in several clinical trials in human cancer patients. For better understanding of the different strains listed in Table 1, we included details of the functional elements of the tet operator system in the names of the rVACV strains as follows.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies it was shown that a recombinant VACV, GLV-1h68, leads to inhibition of tumor growth in different types of human cancers as well as canine mammary cancer (21)(22)(23)(24)(25)(26)(27)(28). In this study we wanted to improve the anti-tumor potency of this virus by constructing a derivative which carries a gene for a Walker A motif mutant (K237E) of Cdc6.…”
Section: Resultsmentioning
confidence: 99%
“…injection of GLV1h68 led to tumor regression of subcutaneous GI-101A human breast cancer xenografts. Furthermore, GLV-1h68 was used to successfully treat different types of human cancers as well as canine mammary cancers (22)(23)(24)(25)(26)(27)(28). In the present study we intended to further enhance the promising antitumor potential of GLV-1h68 without decreasing its safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation